Improvement of Functional Properties of Egg White by High-pressure Homogenisation with Xylo-Oligosaccharide and Its Application in Ice Creams - Lingzhi WEI; Yaotong LIU; Yujie CHI; Yuan CHI (Shipin gongye ke-ji)
Traditional commercially available egg liquids lack specificity, and in order to enhance the specific use of egg liquid bases for the needs of ice cream production, this research was dedicated to the development of egg white bases for ice cream. The effects of high-pressure homogenization (HPH) combined with xylooligosaccharides (XOS) on the foaming properties, emulsifying properties, and protein structure of egg white were investigated. Results showed that compared with untreated egg white, the treatment with 40 MPa HPH for 3 cycles combined with 2.5% (w/v) XOS significantly improved the emulsifying activity by 38.93%, emulsifying stability by 319.90%, foaming ability by 182.85%, and foam stability by 25.03%. The surface hydrophobicity was increased by 124.91%, and the increase in hydrophobicity was found to promote the improvement of emulsifying and foaming properties. In the secondary structure, the relative contents of α-helix and random coil were increased, while the relative contents of β-sheet and β-turn were decreased, indicating that the proteins became more disordered. It was observed by scanning electron microscopy (SEM) and optical microscopy that the egg white particles became more uniform after treatment. Afterwards the ice creams made using this complex egg white liquid showed an increase in apparent viscosity, a decrease in average particle size, improved expansion and melting rates. This study showed that high pressure homogenization with synergistic xylo-oligosaccharides has great potential as a method to improve the emulsification and foaming properties of egg white liquids, and could be used to make food-specific egg white liquids in actual production.